The Art Book. (London : Phaidon, 1994)
Winner of the Illustrated Book of the Year award in 1994, The Art Book has been an outstanding success and has become a well-known landmark in the art book world. Now published in over twenty different languages and in a miniature edition, it has received rave reviews from numerous newspapers and magazines and has made many appearances on the bestseller lists. Complemented by The 20th Century Art Book and The American Art Book, its unique approach brings art alive. An A to Z guide to 500 great painters and sculptors from medieval to modern times, it debunks art-historical classifications by throwing together brilliant examples of all periods, schools, visions and techniques. Each artist is represented by a full-page colour plate of a definitive work, accompanied by explanatory and illuminating information on the image and its creator. Glossaries of artistic movements and technical terms are included, making this a valuable work of reference as well as a feast for the eyes. By breaking with traditional classifications, The Art Book presents a fresh and original approach to art: an unparalleled visual sourcebook and a celebration of our rich and multi-faceted culture.
Keywords: Kunst